2007
DOI: 10.1682/jrrd.2006.07.0079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of co-occurring disorders on employment outcomes in a multisite randomized study of supported employment for people with severe mental illness

Abstract: Abstract-Effects of co-occurring disorders on work outcomes were explored among individuals with severe mental illness who were participating in a multisite randomized study of supported employment. At seven sites, 1,273 people were randomly assigned to an experimental supported employment program or a control condition and followed for 2 years. Multivariate regression analysis examined work outcomes including earnings, hours worked, and competitive employment, as well as whether psychiatric disability was dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 53 publications
5
26
0
1
Order By: Relevance
“…Other studies confirmed the negative impact of presence of co-morbidity on work outcome [19][20][21][22]. Although in our study the presence of one co-morbid condition failed to reach significance, the trend is showing decreased odds on higher work ability.…”
Section: Discussionsupporting
confidence: 68%
“…Other studies confirmed the negative impact of presence of co-morbidity on work outcome [19][20][21][22]. Although in our study the presence of one co-morbid condition failed to reach significance, the trend is showing decreased odds on higher work ability.…”
Section: Discussionsupporting
confidence: 68%
“…Disability type is associated with acceptance in the workplace, with degree of stigmatization mediating the strength of that association (Carpenter and Paetzold, 2013;McLaughlin et al, 2004). Workers with invisible disabilities, most notably mental and psychiatric impairments, experience more stigmatization and related prejudice than people with other types of disabilities (Beck et al, 1998;Cook et al, 2007;Dunn, Wewiorski, & Rogers, 2008;Sanderson & Andrews, 2006;Scheid, 2005). Supervisor attitudes towards Accommodations for severe disabilities are more likely to be perceived as by management as costly and disruptive to the workplace, diminishing the likelihood of a favorable decision (Jackson et al, 2000;Powell & Mainiero, 1999;Unger & Kregel, 2003).…”
Section: Hypothesis Development Hypotheses 1-6: Attitudes Component Omentioning
confidence: 99%
“…Employer sponsored accommodations can assist these workers in their Breward, "Predictors of the Granting of Accommodations" CJDS 6.4 (November 2017) 57 efforts to maximize their participation in the labour force. For example receipt of accommodations in competitive and supported employment contexts has been associated with job retention (Campolieti, 2005;Campolieti, 2009;Cook et al, 2007), morale, productivity, and ability to complete work tasks Yeager et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…O suporte para uma rápida pesquisa e colocação no mercado de trabalho foi bem documentada pelos estudos revistos por e este princípio tem sido vastamente aceite pela maioria da comunidade da reabilitação (e.g., Cook, Razzano, Burke-Miller, Blyer, Leff, & Mueser, 2007;Crowther, Marshall, Bond, & Huxley, 2001).…”
Section: Rápida Pesquisa De Empregounclassified